Origins of sound change - Yu, Alan C. L (Oxford University Press, 2013)
Ebook from Oxford Scholarship Online; Includes bibliographical references and indexes; Pt. 1. What is phonologization? Enlarging the scope of phonologization / Larry M. Hyman -- The role of entropy and surprisal in phonologization and language change / Elizabeth Hume and FreÌdeÌric Mailhot -- pt. 2. Phonetic considerations. Phonetic bias in sound change / Andrew Garrett and Keith Johnson -- From long to short and from short to long: perceptual motivations for changes in vocalic length / Heike Lehnert-LeHouillier -- Inhibitory mechanisms in speech planning maintain and maximize contrast / Sam Tilsen -- Developmental perspectives on phonological typology and sound change / Chandan Narayan -- pt. 3. Phonological and morphological considerations. Lexical sensitivity to phonetic and phonological pressures / Abby Kaplan -- Phonologization and the typology of feature behavior / Jeff Mielke -- Rapid learning of morphologically conditioned phonetics: vowel nasalization across a boundary / Rebecca Morley -- pt. 4. Social and computational dynamics. Individual differences in socio-cognitive processing and the actuation of sound change / Alan C.L. Yu -- The role of probabilistic enhancement in phonologization / James Kirby -- Modeling the emergence of vowel harmony through iterated learning / FreÌdeÌric Mailhot -- Variation and change in English noun/verb pair stress: data and dynamical systems models / Morgan Sonderegger and Partha Niyogi -- References -- Language index -- Subject index